Managing hazards, reducing risks and increasing investments in agriculture : some perspective : critical analysis of policy issues for repositioning agriculture in the Caribbean (IICA Port of SpainTT, 2007)
Explores the implications for the Caribbean Community of three critical issues relating to 'agricultural repositioning'. These critical issues relate to two of these constraints viz. 'deficient and uncoordinated risk management measures' and 'limited financing and new investments'.
Keywords: DISASTERS